2020
DOI: 10.1111/faf.12514
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of the coast‐wide decline in survival of West Coast Chinook Salmon (Oncorhynchus tshawytscha,Salmonidae)

Abstract: We collated smolt-to-adult return rate (SAR) data for Chinook salmon from all available regions of the Pacific coast of North America to examine the large-scale patterns of salmon survival. For consistency, our analyses primarily used coded wire tag-based (CWT) SAR estimates. Survival collapsed over the past half century by roughly a factor of three to ca. 1% for many regions. Within the Columbia River, the SARs of Snake River populations, often singled out as exemplars of poor survival, are unexceptional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 75 publications
1
30
0
3
Order By: Relevance
“…Downward trends in smolt‐to‐adult return rates of Chinook salmon populations along the northeastern Pacific Ocean support a conclusion of strong effects from the ocean (Welch et al. 2021); however, freshwater carryover effects are not altogether negligible. Studies limited by the mechanisms examined and the samples assumed to represent a whole population could lead to an incomplete understanding of carryover effects.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Downward trends in smolt‐to‐adult return rates of Chinook salmon populations along the northeastern Pacific Ocean support a conclusion of strong effects from the ocean (Welch et al. 2021); however, freshwater carryover effects are not altogether negligible. Studies limited by the mechanisms examined and the samples assumed to represent a whole population could lead to an incomplete understanding of carryover effects.…”
Section: Discussionmentioning
confidence: 60%
“…Even though marine covariates such as the Pacific Decadal Oscillation and NPGO indices generally have stronger associations with ocean survival and recruitment than freshwater covariates Schaller 2010, Kilduff et al 2015), our study found that the river system can have considerable influence on ocean survival. Downward trends in smolt-to-adult return rates of Chinook salmon populations along the northeastern Pacific Ocean support a conclusion of strong effects from the ocean (Welch et al 2021); however, freshwater carryover effects are not altogether negligible. Studies limited by the mechanisms examined and the samples assumed to represent a whole population could lead to an incomplete understanding of carryover effects.…”
Section: Discussionmentioning
confidence: 66%
“…These regime shifts alter fishery quotas and recovery timelines and are associated with the widespread decline of wild Pacific salmonids across the Pacific Northwest (Dorner et al, 2013;Peterman & Dorner, 2012;Teresa A'Mar et al, 2009). Despite marine regime shifts having been frequently observed in Pacific salmonids (Welch et al, 2020), descriptions of freshwater regimes shifts are rare (but see Atlas et al, 2015;Jones et al, 2020;Scheuerell et al, 2020), and relatively few studies have assessed regime shifts in both marine and freshwater contexts. Moreover, studies generally focus on a single species even though salmon rivers often support diverse communities.…”
Section: Introductionmentioning
confidence: 99%
“…We provided evidence that the success of river migration by smolts in the River Endrick was low with only 36% of tagged smolts exiting the mouth of the river. This seems to be a trend emerging across rivers in Scotland (Adams, Unpublished data; Honkanen et al 2021, Lothian et al 2018) but also elsewhere (Flávio, et al 2020a, Flávio et al 2020b, Gibson et al 2015) and other salmonid species (Welch et al 2021, Wilson et al 2021. Undeniably, the process of smolting is a critical phase in the life-cycle of anadromous salmonids and has been associated with substantial mortality rates (Clark et al 2016, Halfyard, et al 2012, Thorstad et al 2012.…”
Section: Discussionmentioning
confidence: 95%